Assessing The Applicability of Servqual Model Across Health Care Settings in Developing Countries - Ayu Chairina Laksmi (Jurnal Aplikasi Bisnis, 2017)
The health care service in developing countries is renowned for its poor service quality. However, interest in health care service quality in developing countries is relatively low compared to that in develop countries. It indicates that there are still unresolved problems about the health care service quality measurement in developing countries. In developed countries, the SERVQUAL model is applied for measuring service quality in numerous health care settings. Hence, the purposes of this study are: (1) to assess the practicality of the SERVQUAL moddel in health care services in developing countries; (2) to develop an improved SERVQUAL model for assessing health care service quality in developing countries; and (3) to investigate who should assess the health care service quality in developing countries. To achieve the purposes of this study, a qualitative research using a secondary case study is carried out. The credibility of the findings is established by reliability and validity check through making raw data used in this study accessible for the reader, writing field notes and also conducting triangulation. Initially, a modified SERVQUAL model is developed from the literature on the subject of health care service quality in developed country. Subsequently, the model is compared to the secondary data used in this study. The results from the data analysis demonstrate that the service dimensions of the SERVQUAL model need to be adjusted to the developing country context. It is also revealed that there are two other important dimensions that need to be incorporate in the SERVQUAL model, which are cost and country specific factor. Hence, the improved SERVQUAL model developed as one of the findings in this study, adds cost and country specific factor into its service dimensions. The final finding of this study demonstratis that both the health care providers and the patients in developing countries are the people who should assess the health care service quality.